Consequences of constitutive deletion of melanin-concentrating hormone-1 receptors for feeding and foraging behaviors of mice - Eiler, William J.A.; Chen, Yanyun; Slieker, Lawrence J.; Ardayfio, Paul A.; Statnick, Michael A.; Witkin, Jeffrey M. (Behavioural brain research, 2017)
•MCH1 −/− mice exhibited increased motivation to obtain food compared to WT mice.•Increased food-seeking in MCH1−/− mice was also observed when behavior was punished.•Feeding in MCH1 −/− mice contrasts in some important dimensions from data reported with MCH1 receptor antagonism. In order to decipher the functional involvement of melanin-concentrating hormone 1 (MCH1) receptors in the control of feeding and foraging behaviors, mice with constitutive deletion of MCH1 receptors MCH1R −/− or knockout (KO) were studied and compared to age-matched littermate control mice (MCH1R +/+ or wildtype (WT)). Several challenges to food-motivated behaviors of food-restricted WT and KO mice were implemented. There were no differences between genotypes in the acquisition of a nose-poke response that produced food or in a discrimination between a response that produced food and one that did not. There were also no genotype differences in the rate of extinction of a food-motivated response. However, during the first day of extinction, foraging behaviors were increased significantly more in KO than in WT mice. Likewise, when the response requirement to obtain food was progressively increased, KO mice made significantly more food-directed responses than WT mice. Although adulteration of food with quinine did not suppress food-directed behavior in either genotype when the mice were food-restricted, manipulation of the degree of food-deprivation resulted in suppression of behavior of WT mice without suppressing the behavior of KO mice. Although response-produced foot shock suppressed food-maintained responding of both WT and KO mice, equipotent levels of shock (based upon psychophysical thresholds) suppressed behavior of WT mice without suppressing behavior of the KO mice. Finally, under a Vogel conflict procedure, KO mice had significantly higher levels of both punished and non-punished food maintained responding. Thus, the data from challenges with both appetitive and noxious stimulus challenges support the conclusion that mice with constitutive deletion of MCH1Rs have increased food seeking motivation that is coincident with their higher metabolism. The data also highlight important differences in the biological impact of MCH1 receptor KO and MCH1 receptor antagonism.